Picasso Paintings, Moon Rocks, and Hand-Written Beatles Lyrics: Adults’ Evaluations of Authentic Objects - Frazier, Brandy N. (2009)
Authentic objects are those that have an historical link to a person, event, time, or place of some significance (e.g., original Picasso painting; gown worn by Princess Diana; your favorite baby blanket). The current study examines everyday beliefs about authentic objects, with three primary goals: to determine the scope of adults’ evaluation of authentic objects, to examine such evaluation in two distinct cultural settings, and to determine whether a person’s attachment history (i.e., whether or not they owned an attachment object as a child) predicts evaluation of authentic objects. We found that college students in the U.K. (N = 125) and U.S. (N = 119) consistently evaluate a broad range of authentic items as more valuable than matched control (inauthentic) objects, more desirable to keep, and more desirable to touch, though only non-personal authentic items were judged to be more appropriate for display in a museum. These patterns were remarkably similar across the two cultural contexts. Additionally, those who had an attachment object as a child evaluated objects more favorably, and in particular judged authentic objects to be more valuable. Altogether, these results demonstrate broad endorsement of "positive contagion" among college-educated adults.